2022
DOI: 10.3390/ani12091169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Proteins in Saliva and Serum in Equine Gastric Ulcer Syndrome Using a Proteomic Approach

Abstract: Changes in the salivary proteome in 12 horses with the two diseases included in equine gastric ulcer syndrome (EGUS), equine glandular gastric disease (EGGD) (n = 6) and equine squamous gastric disease (ESGD) (n = 6), were evaluated using a high-resolution LC-MS/MS analysis of TMT-labelled peptides and compared to 10 healthy control horses. Serum was also analysed for comparative purposes. The comparison between the horses with EGGD and controls showed significant changes in 10 salivary proteins, whereas 36 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Serum and saliva showed different responses in our experimental conditions, with differences in the number of proteins showing significant changes as well as in the pattern of proteins with variations. These discrepancies in the number and types of proteins that change between these fluids have been observed previously in other species and diseases [ 40 , 41 , 42 , 43 ]. Therefore, saliva and serum could present complementary information when analyzed.…”
Section: Discussionsupporting
confidence: 51%
“…Serum and saliva showed different responses in our experimental conditions, with differences in the number of proteins showing significant changes as well as in the pattern of proteins with variations. These discrepancies in the number and types of proteins that change between these fluids have been observed previously in other species and diseases [ 40 , 41 , 42 , 43 ]. Therefore, saliva and serum could present complementary information when analyzed.…”
Section: Discussionsupporting
confidence: 51%
“…One study even showed a correlation between histopathological gastric glandular inflammation to duodenal inflammation, including lymphoplasmacytic inflammation and eosinophilic infiltrate, but not to more distal segments of the GI tract [ 67 ]. This evidence of EGGD as a form of gastritis is supported by evidence of immune upregulation in EGGD, demonstrated by altered protein composition of serum and saliva of horses with EGGD compared to controls [ 89 ]. Further work is needed to deepen the understanding of inflammation in EGGD pathophysiology.…”
Section: Pathophysiologymentioning
confidence: 97%
“…In addition, other biomarkers related to oxidative stress, such as ferric-reducing activity of saliva (FRAS), uric acid (UA), and the advanced oxidation protein products (AOPP) were increased in the saliva of horses with EGGD compared with healthy animals, whereas no significant increase was observed in cases of ESGD [ 8 ]. Moreover, a proteomic approach comparing saliva of horses with ESGD and EGGD showed that proteins related with epithelial regulation, such as serpin B5 and keratins 15 (KRT15) and 4 (KRT4), were upregulated in ESGD compared to EGGD [ 9 ]. Additionally, other salivary biomarkers have been reported to be potentially useful in horses with acute abdominal disease [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%